Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s12031-017-0978-x
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-Dependent Inner Retina Layer Damage and Optic Nerve Degeneration in a NMDA Model

Abstract: The intravitreal injection of N-methyl-D-aspartate (NMDA), a glutamate analogue, is an established model for fast retinal ganglion cell (RGC) degeneration. Yet, NMDA does not cause specific RGC damage. Now, the effects on the whole retina were analyzed. Additionally, the related effects for the structure and apoptotic levels of the optic nerve were investigated. Therefore, different NMDA concentrations were intravitreally injected in rats (20, 40, or 80 nmol NMDA or PBS). At days 3 and 14, Brn-3a RGCs were deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 54 publications
4
27
0
1
Order By: Relevance
“…In contrast, the bipolar cells were not affected after the intravitreal HSP27 application. This finding is in accordance with intravitreal injected S100B or NMDA studies [34,50]. Furthermore, the immunization of HSP27 together with S100B did not impair PKCα + bipolar cells.…”
Section: Further Degeneration and Slightly Changed Retinal Electrophysupporting
confidence: 88%
See 1 more Smart Citation
“…In contrast, the bipolar cells were not affected after the intravitreal HSP27 application. This finding is in accordance with intravitreal injected S100B or NMDA studies [34,50]. Furthermore, the immunization of HSP27 together with S100B did not impair PKCα + bipolar cells.…”
Section: Further Degeneration and Slightly Changed Retinal Electrophysupporting
confidence: 88%
“…Likely, the degeneration of RGCs appears prior to the optic nerve damage. This was also described for the intravitreal injection of NMDA [50]. Currently, we cannot exclude that the degeneration starts in the optic nerve and subsequently leads to a retrograde retinal cell body damage at later points in time.…”
Section: Wallerian-like Degeneration Of the Optic Nervementioning
confidence: 73%
“…71−73 NMDA has shown retinal toxicity at low concentrations ( e.g ., 20 nM) with the degree of inner retina damage corresponding to NMDA concentration. 74 NMDA affects other retina cell types and intravitreal administered NMDA also induces partial optic nerve damage, likely linked to the damage of the inner retina. A 20 mM NMDA injection is an extreme model of retina damage.…”
Section: Resultsmentioning
confidence: 99%
“…This confirmed that intravitreal NMDA injection at 20 mM concentration did not result in photoreceptor damage, which is consistent with previous observations. 74,75 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation